Constructing recreational farm operator strategic leadership in VUCA environment - Hsiao, Chih Yu (Frontiers in Sustainable Tourism, 2025)
In a VUCA environment, especially during crises like COVID-19, recreational farm operators face significant challenges. This study examines how strategic leadership fosters adaptability and innovation among Taiwanese operators, drawing on 20 in-depth interviews with diverse recreational farms. Data triangulation via observations, financial analysis, and semi-structured interviews—guided by Schoemaker et al.'s framework—revealed six pivotal leadership capabilities: anticipation, challenge, interpretation, decision-making, alignment, and learning. These competencies enabled effective strategies such as forecasting market trends, diversifying products, embracing digital transformation, reorganizing processes, and developing new offerings to enhance resilience. Forward-looking decision-making and continuous learning further strengthened operations, ensuring operators could seize opportunities amidst uncertainty. The findings underscore strategic leadership's central role in cultivating adaptability and offer insights for advancing agritourism management worldwide.